The Chipped Stone Assemblage from Hartuv - Rosen, Steven A. (Bulletin of ASOR, 1996)
The chipped stone assemblage from Hartuv is comprised of three basic components: flake tools and associated waste; blade tools, both locally produced and imported; and tabular scrapers. There is little evidence of on-site manufacture. The sickle tools differ somewhat from most Early Bronze Age assemblages but otherwise the assemblage is functionally, technologically, and typologically typical of the Early Bronze Age.